Features of European Union development cooperation towards Mexico 2002-2020. Where is it and where is cooperation heading? - Quevedo Flores, Jorge Antonio (Revista Española de Desarrollo y Cooperación, 2022)
This paper examines the development of the cooperation of the European Union towards Mexico in the last eighteen years. The premise for the development of the work would be: "cooperation in Euro-Mexican relations has been limited and has had few achievements and advances." The starting point is the Global Agreement as the basis of relations between the European Union and Mexico, which includes political dialogue, trade, and cooperation. It then examines the chronological development of EU development cooperation in the period from 2002 to 2020. The final part identifies the opportunities for development cooperation of the European Union in the 2021-2027 programming towards the Latin American region and especially towards Mexico and concludes with some final considerations.
Keywords: cooperation; development; Mexico; European Union; triangular